The Concept of Tamannī in the Qur’an: A Thematic Analysis and Its Relevance for Life in the Digital Age - Eni Hidayanti; Muhyidin Azmi; Siti Asiah (ANWARUL, 2026)
In an era of technological disruption, social media algorithms can amplify tamannī, understood as unrealistic hope or wishful thinking unsupported by practical effort, thereby contributing to digital pathologies such as fear of missing out (FOMO), destructive social comparison, and speculative behavior. This study examines the Qur’anic construction of tamannī to formulate an ethical and corrective framework for addressing these contemporary challenges. Employing qualitative library research and Al-Farmawī’s thematic interpretation (tafsīr mawḍū‘ī) methodology, the study triangulates insights from Tafsīr al-Munīr, Ṣafwah at-Tafsīr, and Tafsīr al-Misbah with contemporary digital psychology literature. The findings indicate that Qur’anic expressions of tamannī, conveyed through layta, hal, and lau, encompass both impossible desires and difficult aspirations concerning worldly life and the afterlife. Analysis of An-Najm: 24, An-Nisā’: 32, Āli ‘Imrān: 143, and Al-Qaṣaṣ: 79 demonstrates that tamannī provides a critical lens for understanding instant gratification, performative success, and the desire for curated online realities without corresponding effort. Continuous digital exposure can intensify existential anxiety, overthinking, and psychological dysmorphia, whereas the Qur’an redirects individuals from passive tamannī toward rajā’: realistic hope grounded in purposeful effort, self-discipline, and trust in God. This reorientation can help individuals regulate expectations, resist destructive social comparison, and critically evaluate curated representations of success. The study contributes a cognitive-spiritual literacy framework that integrates ethical reflection, spiritual discipline, and theological awareness to promote digital well-being by transforming tamannī into constructive aspiration, responsible action, and grounded hope.